Eidi - Arias-Bastos, Michael (Instituto Tecnológico de Costa Rica., 2011)
The emergence of the Constructivist approach and its idea that students “construct” their own learning has created a shift in the educational paradigm. Within this new vision of the learning process, teachers are expected to play the role of a facilitator, whose job is to promote spaces for social interactions so students can develop their own knowledge. In this regard, it must be consider that a suitable environment for learning includes not only the subjective aspects or materials, but also involves the physical space, which provides the place where social interactions and the development of materials will improve the learning process. Therefore, the present Graduation Thesis aims to provide an educational proposal that incorporates elements that serve to enhance learning, such as creating recreational and interaction spaces that invite students to stay in the institution, to socialize, to exchange ideas, to seek group solutions, and to unwind in a pleasant atmosphere.
Diseño Arquitectónico
Propuesta de diseño nueva sede de la Escuela de Diseño Industrial del ITCR
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2011.
Keywords: Instituto Tecnológico de Costa Rica Escuela de Diseño Industrial; Espacio en arquitectura; Arquitectura bioclimática; Proyectos arquitectónicos; Diseño Arquitectónico; Arquitectura